Transformatif Pembelajaran Berbasis Literasi dan Numerasi Di Madrasah Ibtidaiyah Negeri 2 Mojokerto - Ninik Evianah (ZAHRA: Research and Tought Elementary School of Islam Journal, 2023)
Literacy and numeracy-based transformative learning at Madrasah Ibtidaiyah in thematic learning from grades 1-6 can be implemented by providing stimulus to students. Literacy and Numeracy are important skills that primary school students must possess to support their abilities in education, achieve their potential, and participate in society. This article will review the concept of transformative learning based on literacy and numeracy for Madrasah Ibtidaiyah Negeri 2 Mojokerto. Transformative learning theory and the concept of numeracy literacy are described as developing learning concepts because transformative learning not only transfers knowledge but also makes changes, especially understanding literacy and numeracy.